2015
DOI: 10.1177/1352458514559297
|View full text |Cite
|
Sign up to set email alerts
|

Validity of four screening scales for major depression in MS

Abstract: While all of the scales performed well in terms of their sensitivity and specificity, the availability of the PHQ-9 in the public domain and its brevity may enhance the feasibility of its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 33 publications
(42 reference statements)
3
79
0
7
Order By: Relevance
“…2015) and showed good accuracy for the CES-D, the PHQ (9 and 2), and the HADS. Since the PHQ is available free of charge, it might therefore be particularly interesting.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…2015) and showed good accuracy for the CES-D, the PHQ (9 and 2), and the HADS. Since the PHQ is available free of charge, it might therefore be particularly interesting.…”
Section: Discussionmentioning
confidence: 94%
“…This approach is, therefore, highly accurate as a screening tool, although a more recent study reported lower estimates of specificity and sensitivity for this instrument (Patten et al. 2015). Moreover, it does not provide a quantitative score of depression severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For depressive symptom severity assessment, the well-known Beck Depression Inventory and the Hospital Anxiety and Depression Scale have both been diagnostically evaluated in MS patients 42,44 and have psychometric properties that are sensitive to change. This sensitivity has, however, not been tested specifically in MS patients.…”
mentioning
confidence: 99%